The Effect of Promotion and Service Quality on Purchase Decisions Through Purchase Interest on Grabfood Application in East Jakarta - Natalia Tobing; Wagiarto Hoesin; Iwan Kurniawan Subagja (The Institute of Academic Research and Publication (IARP), 2022)
This study aims to: 1) Analyze the effect of promotion on purchase interest, 2) Analyze the effect of service quality on purchase interest, 3) Analyze the effect of promotion and service quality on purchase interest 4) Analyze the effect of promotion on purchasing decisions, 5) Analyze the effect of service quality on purchasing decisions 6) Analyze the effect of promotion and service quality on purchasing decision, 7) Analyze the effect of purchase interest on purchasing decisions, 8) analyze the effect of promotion and service quality on purchasing decisions through purchase interest. This research was conducted on customers' GrabFood applications. The number of samples obtained was 100 respondents. The sampling technique used a random technique with analytical methods using descriptive analysis methods and path analysis. The result show that: 1) there is an effect of promotion on purchase interest, 2) there is an effect of service quality on purchase interest, 3) there is an effect of promotion and service quality on purchase interest, 4) there is an effect of promotion on purchasing decisions, 5) there is an effect of service quality on purchasing decisions, 6) there is an effect of purchase interest on purchasing decisions, 7) there is an effect of promotion and service quality on purchasing decisions, 8) purchase interest cannot mediate to increase the effect of promotion and quality service on consumer purchasing decisions on the application GrabFood in Jakarta Timur.